Conversion of the knowledge in a federal university on the basis of Nonaka e Takeuchi - Begnini, Sergio (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
This study focuses on the study of the conversion of knowledge in the administrative area of a federal university, based on the SECI model of Nonaka and Takeuchi. The main objective is to analyze how knowledge within the administration, is created and diffused at the Federal University of the Border South, from the point of view of its leaders, the SECI model of Nonaka and Takeuchi perspective. It is a study with a quantitative approach and methodological procedures bibliographic and field research. Structured questionnaire closed and no disguise was applied to managers who made up the sample, intentionally chosen not random. It was found that at the Universityin question, in the view of their leaders, knowledge tends to be created and disseminated following the four conversion modes: socialization, externalization, combination, internalization. It concludes that the conversion modes -socialization and externalization -seem more consolidated while -combination and internalization -seem to need maturity.